The Effect of Deficit Irrigation Strategies on the Efficiency From Plant to Essential Oil Production in Peppermint (Mentha piperita L.) - Akbarzadeh, Ali; Shahnazari, Ali (Frontiers in Water, 2021)
The effect of deficit irrigation on water productivity in the water supply and utilization chain has been computed, employing a systematic and quantitative approach. By applying such investigations, weaknesses and strengths of deficit irrigation strategies could be revealed, and actions and measures could be implemented to improve water productivity as much as possible. The peppermint plants were subjected to regulated deficit irrigation (RDI) and partial root-zone drying (PRD). Peppermint was cultivated under full irrigation (FI, control) and RDI treatments including RDI85, RDI70, RDI55, and RDI40, receiving 85, 70, 55, and 40% of FI treatment, respectively; PRD techniques including PRD70, PRD55, and PRD40, receiving 70, 55, and 40% of FI treatment in one side of root-zone at each irrigation event, respectively during two cutting seasons. There was no significant improvement in leaves weight and dried yield step by applying deficit irrigation treatments. Leaves and aerial parts from the whole plant and dried yield as the main source of essential oil had the weakest function, which should be optimized to adjust and gain more efficiency. In the essential oil yield step, as a final procedure, the highest improvements observed in PRD55 treatment with 90% improvement in efficiency compared to control treatment. According to the results and calculating water productivity, PRD55 treatment improved water productivity by 179% compared to the control treatment. Two way ANOVA analysis between deficit volume and deficit applying method, showed that total water productivity, were affected (increased) significantly by deficit applying method. This implies the contribution of the PRD technique to enhance more signals than RDI based signals, which resulted in more improvements in secondary metabolism production in peppermint.